A rare cause of dyspnea: Primary large B cell lymphoma causes giant cardiac mass. Issue 10 (29th September 2022) - Aksu, Uğur; Korucu, Cem; Atilgan, Kivanç; Aybek, Tayfun; Gökaslan, Çiğdem Özer; Aksu, Derya; Özdemir, Çiğdem
Abstract: Cardiac lymphoma (CL) is a rare and life‐threatening clinical condition. Most cases are diagnosed late period. Although the definitive diagnosis is made by biopsy, a biopsy could not be performed in most cardiac masses due to the high mortality rate and therefore the exact incidence is not known. In this case report, we present a case of giant CL filling both the pericardial area and right heart cavities and treated with surgical resection in a previously healthy male patient who presented with symptoms of heart failure.